2022
DOI: 10.1002/ejoc.202200270
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Activity Studies of Nitroreductase‐Responsive Near‐Infrared Heptamethine Cyanine Fluorescent Probes

Abstract: Two new classes of near‐infrared molecular probes were prepared and shown to exhibit “turn on” fluorescence when cleaved by the nitroreductase enzyme, a well‐known biomarker of cell hypoxia. The fluorescent probes are heptamethine cyanine dyes with a central 4‘‐carboxylic ester group on the heptamethine chain that is converted by a self‐immolative fragmentation mechanism to a 4‘‐caboxylate group that greatly enhances the fluorescence brightness. Each compound was prepared by ring opening of a Zincke salt. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Notable among this series, ethyl ester 3h is essentially nonemissive; by contrast, the carboxy variant 3f , likely as the anionic carboxylate, is bright (63,900) with a λ abs of 748 nm. Of note, prior work by Smith and coworkers found that a related 4-nitro benzyl ester was also nearly nonemissive, which allowed it to be employed for hypoxia-responsive imaging. , We also find that heteroaromatic-substituted heptamethine indocyanines exhibit dramatic bathochromic shifts but are essentially nonemissive ( 3q–3s ). This result contrasts with findings on the rhodamine scaffold where imidazole and imidazolium substituents at the meso position do not compromise photophysical properties .…”
Section: Methods Development and Substrate Scopesupporting
confidence: 59%
See 3 more Smart Citations
“…Notable among this series, ethyl ester 3h is essentially nonemissive; by contrast, the carboxy variant 3f , likely as the anionic carboxylate, is bright (63,900) with a λ abs of 748 nm. Of note, prior work by Smith and coworkers found that a related 4-nitro benzyl ester was also nearly nonemissive, which allowed it to be employed for hypoxia-responsive imaging. , We also find that heteroaromatic-substituted heptamethine indocyanines exhibit dramatic bathochromic shifts but are essentially nonemissive ( 3q–3s ). This result contrasts with findings on the rhodamine scaffold where imidazole and imidazolium substituents at the meso position do not compromise photophysical properties .…”
Section: Methods Development and Substrate Scopesupporting
confidence: 59%
“…Progress in optical probe discovery requires progress in the synthetic methods to assemble them. The ability to substitute the heptamethine cyanine chromophore is critical because unsubstituted variants are prone to dye–dye interactions and ROS-mediated chemistries. , Strategies that use cyclic ketone starting materials have been broadly adopted, despite inherent limitations to the range of accessible chromophore substituents. ,, The recent discovery that dinitrophenyl-pyridinium salts can act as cyanine precursors provides a valuable means to diversify the chromophore and has been applied by several groups with significant success. ,,,,,, However, this approach is difficult to apply to certain chromophore and indolenine substituent patterns. We therefore considered alternative pyridine activation strategies, leading to the studies reported here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the subsequent collaboration with us, Smith and co-workers explored the possibilities to red-shift both absorption and emission maxima of these probes. [49] In this quest, the first developed class of probes was a homologous pair inspired by ICG (Fig. 4B) which incorporated benzoindolines as the terminal heterocycles.…”
Section: Hypoxia Probesmentioning
confidence: 99%